Interreligious Education Model: The Model of Religious Education of Teachers at SMAK BPK PENABUR Jakarta in Responding the Policy of Compulsory Religious Education in Indonesia - Nenohai, Jear; Limbu, Anggun Permata Indah (Satya Widya: Jurnal Studi Agama, 2024)
Research on compulsory religious education policies in Indonesia, criticized for their normative and pedagogically lacking nature, primarily functions as religious instruction due to their mono-religious focus (Bagir: 2011, Suhadi et al.: 2013, Yusuf and Sterkens: 2016). Consequently, the existing religious education model in Indonesia falls short in fostering tolerance and mutual respect among students of diverse faiths, particularly within the school setting. The mono-religious approach not only presents pedagogical challenges but also hinders the development of dialogue between teachers and students of differing beliefs. This paper attempts to narrate teachers' experiences in teaching religious education to students of various religions, utilizing qualitative methods such as literature review and interviews. The study focuses on Christian religion teachers at SMAK BPK PENABUR Jakarta. The findings reveal that teachers face challenges in bridging knowledge gaps between themselves and students, prompting the need for negotiation and transformation of the religious education classroom into an interreligious education space, fostering dialogue between teachers and students of different faiths.